ISMA’IL RAJI AL-FARUQI THE FOUNDING FATHER ISLAMISASI PENGETAHUAN - Sholehuddin, M. Sugeng (IAIN Pekalongan, 2010)
The presence of Ismail Raji al-Faruqi’s ideas who had dared to offer a rationale for Islamizing science is a startling breakthrough at that time. However, what was imagined by Muslim intellectuals at that time was that the idea was very heavy to be resolved immediately. Ismail Raji al-Faruqi noted that Muslims were subjugated by the West, all life aspects, such as military, political, economic, legal, and educational system had been exploited. Therefore, Ismail Raji al-Faruqi wanted to restore all those channels with the religious spirit of Islam. In the building of modern civilization Ismail Raji al-Faruqi did not depart from zero, in spite of that he departed from the existing civilization by organizing infilteration values derived from monotheism.